Production of xylooligosaccharides from corncob using a crude thermostable endo-xylanase from Streptomyces thermovulgaris TISTR1948 and prebiotic properties - Boonchuay,P. (Springer Netherlands, 2015)
© 2014, The Korean Society of Food Science and Technology and Springer Science+Business Media Dordrecht. Production of xylooligosaccharides (XOs) from corncob using the thermostable endo-xylanase from Streptomyces thermovulgaris TISTR1948 was investigated using KOH pretreatment, followed by enzymatic hydrolysis. The optimal reaction time for production of XOs was 12 h, after which xylobiose comprised a majority of products, and a low xylose content was observed. The optimal conditions for production of XOs were studied using a central composite design. At an enzyme concentration of 129.43 U/g of substrate, 53.80°C, and pH 6.17, the yield of XOs reached 162.97 mg/g of substrate or 752.15 mg/g of hemicellulose in KOH-pretreated corncob. The prebiotic properties of XOs derived from corncob were also investigated using in vitro fermentation of those XOs with the known probiotic strains Lactobacillus casei TISTR1463, L. lactis TISTR1464, and L. plantarum TISTR1465. XOs derived from corncob were comparable to commercial XOs for an ability to enhance the growth of the specified probiotic lactobacilli.